Analyzing the Effect of Dried Shrimp on the Flavor of Sheep Bone Soup Through Sensory Evaluation Combined with Untargeted Approaches - Qiuyu Zhu; Lili Zhang; Xingming Sun; Baoguo Sun; Yuyu Zhang (Foods)
Dried shrimp is a popular dietary ingredient that is often included in appetizer soups, stir-fry dishes, or other stews to improve the umami taste. The effects of adding dried shrimp on the sensory characteristics and taste components of sheep bone soup were investigated through sensory evaluation and untargeted approaches. The results of the single-factor and orthogonal experiments showed that the flavor qualities of sheep bone soup were optimal under the following conditions: 30% dried shrimp added, a 1:4.5 material–water ratio, and 2.7 h of stewing time. Sensory analysis showed a significant increase in the aroma, umami, kokumi, and texture intensity of the optimized sheep bone soup with dried shrimp. The untargeted approach combined with multivariate statistical analysis showed that compounds with a sweet taste (Lys and Ser), a umami taste and umami enhancement (Ala-Leu, Glu-Pro, Glu-Glu, Asp-Phe, pyroglutamic acid, and cinnamic acid), a bitter taste (Gly-Leu, Leu-Leu, Ile-Lys, and taurine), a kokumi taste (γ-Glu-Met, γ-Glu-Leu, γ-Glu-Ile, N-acetylmethionine, and N-acetylphenylalanine), a sour taste (malic acid), and a popcorn-like aroma (2-acetylthiazole) contributed significantly to the flavor enhancement of sheep bone soup. In addition, the contribution of Ac-Ser-Asp-Lys-Pro could not be ignored. These results contribute to a better understanding and improvement of the flavor qualities of sheep bone soup.